PENERAPAN ECO-ARCHITECTURE PADA SURFING CLUB CENTER DI PANTAI SESEH: Indonesia - Putu Gede Raditya Juniarta; Ni Wayan Nurwarsih; I Kadek Merta Wijaya; I Wayan Wirya Sastrawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2025)
This research aims to design a Surfing Club Center that is integrated with the Eco-Architecture approach in Seseh Beach, Cemagi, Badung Regency. The background of this research is the high potential of Seseh Beach as a surfing tourism destination that has not been supported by integrated facilities, prevention of beach accidents, and means of developing tourist villages in Cemagi. The research method involves secondary data analysis and field observation to understand the needs of tourists and the characteristics of the location. This design emphasizes the application of environmentally friendly design, such as the use of local materials, energy-efficient building systems, and adaptation to coastal environmental conditions and local architecture. The design results include surf training facilities in the form of theory and training areas with flowriders, surfing community gathering areas, lodging, and tourist support facilities. The implementation of the Eco-Architecture approach aims to create facilities that support environmental sustainability while increasing tourist attractions. This study contributes to the sustainable development of beach tourism in bali.